PRINCIPAL INSPIRATORY MUSCLE OF UROMASTIX HARDWICKII - Azeem, Muhammad Abdul; Gul, Saima; Ahmed, Sadaf; Al-Harbi, Waheeb Dakheelullah; Ali Rakkah, Nabeeh Ibrahim (Pakistan Journal of Physiology, 2010)
Variations in the musculoskeletal system exist in different classes of animal. The chest muscles are specifically modified due to modifications in axial skeleton in each vertebrate class. In addition, diaphragm is one of the main respiratory muscle in mammals which is absent in reptiles, specifically lizards, having different modes of respiration, e.g., buccal, axial and hepatic piston. Additionally, they do not breathe well during locomotion. Since, sternum and chest cage both are properly developed in these animals, therefore, they must be having an alternate chest muscle involved in the act of inspiration. The purpose of this study was to identify the principal inspiratory muscle in the chest of the reptile Uromastix. Repeated dissections, visual observations and electrical stimulation of the exposed but intact chest muscle (pectoralis/supracoracoideus) of Uromastix have demonstrated three major parts in it. Being, superior (S), middle (M) and inferior (I), identified on the basis of their colour, position and response to electrical stimulation. Accordingly, the locomotor action of these parts S, M and I are forceful, mild and feeble adduction of fore limb, respectively. While, its inferior part (I) additionally showed further sub-divisions into 3 portions, Is, Im and Ii. On electrical stimulation, one of them, i.e., Ii portion of the chest muscle of Uromastix demonstrated rib-cage elevation and thus named, ‘Rib Cage Elevator’, helping inspiration. It is concluded that chest muscle of Uromastix play dual role, in locomotion as well as respiration.